2002
DOI: 10.1103/physreve.65.046209
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Lyapunov exponent using quantum mechanics

Abstract: We study the time evolution of two wave packets prepared at the same initial state, but evolving under slightly different Hamiltonians. For chaotic systems, we determine the circumstances that lead to an exponential decay with time of the wave packet overlap function. We show that for sufficiently weak perturbations, the exponential decay follows a Fermi golden rule, while by making the difference between the two Hamiltonians larger, the characteristic exponential decay time becomes the Lyapunov exponent of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 33 publications
4
108
0
Order By: Relevance
“…Extensive investigations have been performed in recent years to understand the decaying behaviors of the LE [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In chaotic systems, roughly speaking, the LE has a Gaussian decay [23] below a perturbative border and has an exponential decay M L (t) ∝ exp(−Γt) above the border.…”
Section: Lochmidt Echo and Fidelity For The Dicke Model At Qptmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive investigations have been performed in recent years to understand the decaying behaviors of the LE [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In chaotic systems, roughly speaking, the LE has a Gaussian decay [23] below a perturbative border and has an exponential decay M L (t) ∝ exp(−Γt) above the border.…”
Section: Lochmidt Echo and Fidelity For The Dicke Model At Qptmentioning
confidence: 99%
“…The dramatic change of the wave function at a QPT implies a fast decrease of the fidelity when approaching the critical point. Another metric quantity useful for characterizing the occurrence of a QPT is the quantum Loschmidt echo (LE) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], which provides a measure to the stability of the quantum motion under * Electronic address: wgwang@ustc.edu.cn two slightly different Hamiltonians. This quantity exhibits a dramatic change in its decaying behavior in the neighborhood of critical points.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a relationship between this quantity and the Lyapunov exponent that characterizes the classical chaos has been established analytically by using the semiclassical theory by Jalabert and Pastawski [3], which has been confirmed numerically in several models [4][5][6][7][8][9]. Therefore, this quantity has attracted a great attention from the community of quantum chaos [10][11][12][13], It has been shown that several regimes exist.…”
Section: Introductionmentioning
confidence: 99%
“…This profile plays a fundamental role also in the analysis of system stability for few-body systems subject to a sudden perturbation [10], such as the onset of an external field, and has been studied extensively in the context of quantum chaos and dynamical localization [11,12]. Quite generally the LDOS is related to the survival probability of the unperturbed eigenstate [4,10,13], and there has been considerable recent effort to understand the conditions under which the LDOS width determines the rate of fidelity decay under imperfect motion-reversal ("Loschmidt echo") [13,14,15,16].A number of theoretical methods have been devised to characterize the LDOS for complex systems. These methods include banded random matrix models [3,17,18,19], models of a single-level with constant couplings to a "picketfence" spectrum [4,20], and perturbative techniques with partial summations over diagrams to infinite order [21].…”
mentioning
confidence: 99%
“…This profile plays a fundamental role also in the analysis of system stability for few-body systems subject to a sudden perturbation [10], such as the onset of an external field, and has been studied extensively in the context of quantum chaos and dynamical localization [11,12]. Quite generally the LDOS is related to the survival probability of the unperturbed eigenstate [4,10,13], and there has been considerable recent effort to understand the conditions under which the LDOS width determines the rate of fidelity decay under imperfect motion-reversal ("Loschmidt echo") [13,14,15,16].…”
mentioning
confidence: 99%